2012
DOI: 10.20452/pamw.1198
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar echinococcosis of the liver: a single center experience

Abstract: INTROduCTION In humans, alveolar echinococcosis (AE) of the liver is caused by canine tapeworm called Echinococcus multilocularis. The disease is most prevalent in the northern hemisphere and in the eastern part of Turkey. ObjECTIvEs The aim of the study was to review the natural history of AE and its clinical and radiological features. PATIENTs ANd mEThOds The retrospective study involved 23 patients (10 men, 13 women), aged 34-75 years with AE who had been referred to our liver disease clinic in the past 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Ozyurtkan et al [ 6 ] found that elevated leukocytes are more common in cases with hydatid cyst rupture. In the present study, 100% (9/9) of cases with leukocytosis had cyst rupture, which is consistent with previous findings [ 6 , 11 ] and indicates the presence of secondary infection of the CE3 lesion through cyst wall rupture. Parallel infections might have influenced measured blood parameters such as leucocyte count.…”
Section: Discussionsupporting
confidence: 93%
“…Ozyurtkan et al [ 6 ] found that elevated leukocytes are more common in cases with hydatid cyst rupture. In the present study, 100% (9/9) of cases with leukocytosis had cyst rupture, which is consistent with previous findings [ 6 , 11 ] and indicates the presence of secondary infection of the CE3 lesion through cyst wall rupture. Parallel infections might have influenced measured blood parameters such as leucocyte count.…”
Section: Discussionsupporting
confidence: 93%
“…Less commonly, cysts develop in the lungs causing respiratory symptoms or pain [99]. E. multilocularis is associated with eosinophilia less frequently that with E. granulosis , but rarely, mild eosinophil elevations may be seen [111-114]. …”
Section: Eosinophilia In Indigenous Population (Immigrant/refugeementioning
confidence: 99%
“…The treatment of the advanced HAE, especially the necessity of aggressive operations, is disputed. [15][16][17] In the retrospective study, we analyzed 42 patients with advanced HAE treated with palliative resection, palliative nonresective procedures, OLT, or albendazole therapy alone. These patients were not randomized and that treatments were based on disease presentations, individual wishes, and physician choices as well.…”
Section: Discussionmentioning
confidence: 99%
“…The management of advanced HAE, especially the necessity of aggressive operations, like palliative resection and orthotopic liver transplantation (OLT), remains controversial. [15][16][17] …”
Section: Introductionmentioning
confidence: 99%